Neurofilament light-chain response during therapy with antisense oligonucleotide tofersen in SOD1-related ALS: treatment experience in clinical practice: clinical research short report - Meyer, Thomas; Schumann, Peggy; Weydt, Patrick; Petri, Susanne; Koc, Yasemin; Spittel, Susanne; Bernsen, Sarah; Günther, René; Weishaupt, Jochen H.; Dreger, Marie; Kolzarek, Felix; Kettemann, Dagmar; et al. (Muscle & nerve, 2023)
Introduction/Aims In amyotrophic lateral sclerosis (ALS) caused by superoxide dismutase 1 (SOD1) gene mutations (SOD1-ALS), the antisense oligonucleotide tofersen had been investigated in a phase III study (VALOR) and subsequently introduced in an expanded access program. In this study we assess neurofilament light chain (NfL) before and during tofersen treatment. Methods In six SOD1-ALS patients treated with tofersen at three specialized ALS centers in Germany, NfL in cerebrospinal fluid (CSF-NfL) and/or serum (sNfL) were investigated using the ALS Functional Rating Scale Revised (ALSFRS-R) and ALS progression rate (ALS-PR), defined by monthly decline of ALSFRS-R. Results Three of the six SOD1-ALS patients reported a negative family history. Three patients harbored a homozygous c.272A > C, p.(Asp91Ala) mutation. These and two other patients showed slower progressing ALS (defined by ALS-PR <0.9), whereas one patient demonstrated rapidly progressing ALS (ALS-PR = 2.66). Mean treatment duration was 6.5 (range 5 to 8) months. In all patients, NfL decreased (mean CSF-NfL: −66%, range −52% to −86%; mean sNfL: −62%, range −36% to −84%). sNfL after 5 months of tofersen treatment was significantly reduced compared with the nearest pretreatment measurement (P = .017). ALS-PR decreased in two patients, whereas no changes in ALSFRS-R were observed in four participants who had very low ALS-PR or ALSFRS-R values before treatment. Discussion In this case series, the significant NfL decline after tofersen treatment confirmed its value as response biomarker in an expanded clinical spectrum of SOD1-ALS. Given the previously reported strong correlation between sNfL and ALS progression, the NfL treatment response supports the notion of tofersen having disease-modifying activity.
Online veröffentlicht: 16. März 2023
Gesehen am 15.07.2024